Correlates of Segmental Pulse Wave Velocity in Older Adults: The Atherosclerosis Risk in Communities (ARIC) Study - Meyer, Michelle L; Tanaka, Hirofumi; Palta, Priya; Cheng, Susan; Gouskova, Natalia; Aguilar, David; Heiss, Gerardo (American journal of hypertension, 2016)
Carotid-femoral PWV (cfPWV) is a well-established measure of central arterial stiffness, while brachial-ankle PWV (baPWV) is being used more frequently in East Asian countries. Few studies have simultaneously characterized the distributions and correlates of segment-specific PWV measures and their associations with cardiovascular risk factors. We evaluated segment-specific PWV (cfPWV, baPWV, and femoral-ankle (faPWV)) in 4,974 older-aged African American and Caucasian adults in the community-based Atherosclerosis Risk in Communities (ARIC) Study using a standardized protocol and the OMRON VP-1000 Plus system. We examined the distribution and multivariable-adjusted correlates of PWV measures by race and sex. Mean age ranged from 74 ± 5 to 76 ± 5 years across race-sex groups. In all race-sex groups, cfPWV correlated with baPWV but not with faPWV, and cfPWV and baPWV were higher with age, whereas faPWV was not. Heart rate and systolic blood pressure (SBP) were positively associated and weight was negatively associated with all PWV measures; however, the associations with age, glycated hemoglobin, triglycerides, and high-density lipoprotein (HDL) cholesterol varied by segment and race-sex group. Our findings indicate that cfPWV and faPWV reflect distinct aspects of segment-specific vascular stiffness and their associated profile of cardiovascular risk factors. Even among older adults, age is associated with higher cfPWV and baPWV, but not with faPWV. Understanding factors that ostensibly play a role in increasing arterial stiffness in different arterial territories can inform opportunities for cardiovascular disease (CVD) prevention and risk management.